How ICT Supports the Mathematical Problem-Solving Learning Process of Secondary School Students: A Systematic Literature Review - Ahmad Dzulfikar; Turmudi Turmudi; Tatang Herman; Kusnandi Kusnandi (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: This study aims to systematically examine the role of Information and Communication Technology (ICT) in supporting students’ mathematical problem-solving processes at the secondary school level. It addresses the current gap in the literature by providing a focused synthesis of how ICT is utilized in mathematics education to enhance students’ problem-solving abilities. Methodology: A Systematic Literature Review was conducted following the PRISMA protocol. Articles were sourced from reputable databases, such as Scopus, Taylor & Francis Online (Tandfonline), and Education Resources Information Center (ERIC). Through a rigorous selection process based on relevance and quality criteria, 25 peer-reviewed articles published within the past ten years were analyzed and synthesized. Main Findings: The review reveals that ICT is widely employed to improve the quality of instruction and students’ problem-solving skills in mathematics. ICT supports learning across various topics such as geometry, calculus, and algebra, mainly through visualization tools and interactive simulations. Furthermore, ICT serves multiple roles: as a medium for ICT-assisted instruction, a complement to instructional materials, a platform for online learning, an assessment tool and a resource for student-directed learning, and as an adaptive and diagnostic learning systems. Novelty/Originality of this study: This study contributes a focused and systematic analysis of how ICT specifically enhances mathematical problem-solving at the secondary level, a perspective that has been underrepresented in existing reviews. By identifying the specific functions and impacts of ICT in this context, the study lays the groundwork for future research and development of ICT-based pedagogical strategies in mathematics education.